Fabrication and characterization of osteogenic function of progenitor cell‐laden gelatin microcarriers. Issue 6 (17th December 2021) - Nweke, Chukwuma E.; Stegemann, Jan P.
Abstract: Biomaterial‐based bone regeneration strategies often include a cellular component to accelerate healing. Modular approaches have the potential for minimally‐invasive delivery and the ability to conformally fill complex defects. In this study, spherical gelatin microparticles were fabricated via water‐in‐oil emulsification and were subsequently crosslinked with genipin. Microparticle diameter depended on impeller geometry, and increased stirring rates consistently produced smaller particles with narrower size distributions. Increasing the concentration of gelatin resulted in larger particles with a broader size distribution. Viscoelastic characterization showed that increased gelatin concentration produced stiffer matrices, though the mechanical properties at lower gelatin concentration were more stable across strain rate. Microparticles of 6.0% wt/vol gelatin were then applied as microcarriers for packed‐bed culture of human mesenchymal stromal cells (MSC) at seeding densities of 5.0 × 10 3, 2.5 × 10 4, or 5.0 × 10 4 cells/cm 2 of surface area, in either control or osteogenic medium. Cell viability was uniformly high (>90%) across seeding densities over 22 days in culture. MSC number stayed approximately constant in the 5.0 × 10 3 and 2.5 × 10 4  cells/cm 2 samples, while it dropped over time at 5.0 × 10 4 cells/cm 2 . Alkaline phosphatase activity was significantly upregulated in osteogenic conditions relative to controls at day 15, and absolute calcium deposition was strongly induced by days 15 and 22. However, calcium deposition per cell was highest in the lowest cell density, suggesting an inhibitory effect of high cell numbers. These results show that genipin‐crosslinked gelatin microcarriers can be reproducibly fabricated and used as microcarriers for progenitor cells, which may have utility in treating large and complex bone defects.